Steamboat GOV. PINGREE leaving its winter quarters in Steamboat Slough on the near the mouth of the Klondike River, Yukon Territory, ca. 1899. - Kinsey & Kinsey
Caption on image: "Leaving winter quarters at Steamboat Slough" The Gov. Pingree also operated as the Bonanza King, and was owned at various times by the Yukon Flyer Transportation Company and by the Boston & Alaska Transportation Company. PH Coll 246.109 [Meed journal: "Steamer "Gov. Pingree" of Seattle (renamed "Eldorado") leaving its winter quarters in Steamboat Slough opposite Dawson and the mouth of the Klondike River."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number